A Case Study Of The Correlation Between Ergonomic Risk Factor And Work-Related Musculoskeletal Disorders (Wmsds) Among Workers In Perodua Rawang - Wan Nur Qasrina Aisyah, Wan Mohd Fazamiza (2024)
This case study investigates the correlation between ergonomic risk factors and the prevalence of Work-Related Musculoskeletal Disorders (WMSDs) among workers in the automotive manufacturing sector, focusing on tasks involving the tightening of bolts, nuts, and screws. Data collection was conducted using the Nordic Musculoskeletal Questionnaire (NMQ) and the Rapid Entire Body Assessment (REBA), targeting ergonomic risks such as awkward postures, prolonged static positions, and repetitive motions. The findings revealed high prevalence rates of discomfort in the waist (75.00%) and back (65.91%), followed by significant reports in the shoulders, knees, and wrists, consistent with previous research. Spearman’s rank correlation analysis demonstrated significant relationships between ergonomic risk factors and discomfort levels in body regions such as the lower neck, shoulders, upper arms, wrists, and knees. These findings support the hypothesis that postural risk factors significantly contribute to the prevalence of musculoskeletal discomfort among workers